Geocomplexo: Interação de elementos naturais e sociais - Produção e expansão da cana-de-açúcar na bacia hidrográfica do rio Paranapanema - PR / SP - Braido, Leandro Marcos Herreiro [UNESP] (2015)
Searching for new fuels as alternatives to the fossils ones many countries had developed researches in order to find the best way. Brazil stands out in the worldwide scenario by its sugarcane (Saccharum spp) production, raw material to ethanol synthesis, regard as an agrofuel as its production is typically mono-culture plantations complying with agrobusiness concerns. The chosen area for the thesis was the Paranapanema watershed or, accordingly with National Council of Water Resouces, the Paranapanema UGRHI (Management Unity for Water Resources - Paranapanema) established with 247 counties in a area of 105,921 km². The aim of this study was to characterize the sugar cane production by means of a path sequential analysis and application of the water balance in sector delimited by analogous elements of climate, soils and relief, applying the geocomplex concept. By means of geofacies and geotopos and the relations among biotic, abiotic and anthropic elements in a geographical scale of analysis it was applied the path sequential analysis, as nominated by this study, which is the variation among the types of relief, soils and crops found in a established path between two points. This analysis implies overlapping cartographic basis as to collect soil samples and images from the crops in chosen places in the determined path. Climate characterization was performed by means of a historical series of climate data (precipitation and temperature) from 1970 to 2010...